PENGARUH AKUN DAKWAH YOUTUBE TERHADAP PERILAKU RELIGIUSITAS SISWA DI MAN 2 PALEMBANG - Samsu Rizal; Ahmad Syarifuddin; Syarnubi Syarnubi (PAI RAFAH, 2019)
The problems that will be studied in this study, namely: (1) How is the use of the youtube missionary account of MAN 2 Palembang students? (2) What is the religiosity behavior of MAN 2 Palembang students? (3) Is there influence on the YouTube mission to the religiosity behavior of students of MAN 2 Palembang?While the purpose of this study, are: (1) To find out how the use of students' youtube da'wah mission 2 Palembang, (2) To find out how the religiosity behavior of students of MAN 2 Palembang, (3) To find out whether there is influence of youtube da'wah on religiosity behavior of MAN students 2 Palembang. The data of this study were collected from students of the youtube 2 missionary mission of MAN 2 Palembang as the object of research. The data collection uses the method of observation, questionnaire and documentation. This research is included in the type of quantitative research with data analysis techniques using product moment correlation.Based on the results obtained through the field and calculations using the product moment correlation formula, it can be concluded that: (1) The percentage of users of the youtube missionary account of Palembang MAN 2 students is in the medium category, which is 59%. (2) The percentage of religiosity behavior of Palembang MAN 2 students in the medium category is 59%. (3) There is a significant level of correlation between the youtube da'wah account on the religiosity behavior of students of MAN 2 Palembang with the results of the calculation of the product moment correlation formula obtained that the value of t count is greater than the value of t table with a significant level of 5% and a significant level of 1% which is 0.210 < 8, 35> 0.159